Analysis of red blood cell lifespan and associated influencing factors in anemic dialysis patients - Jiaqing Wu; Bei Wu; Weili Gao; Yan Wang; Li Zhu; Li Bai; Lixia Lu; Ji Feng; Yanyan Shao; Liangying Gan; Huiping Zhao; Chunfang Wang; et al. (Renal Failure)
Introduction Renal anemia is one of the most common complications in dialysis patients. The shortened red blood cell (RBC) lifespan is an important mechanism of renal anemia. This study aims to investigate the RBC lifespan and its influencing factors in anemic dialysis patients.Method Prevalent patients on maintenance hemodialysis or peritoneal dialysis, treated with anti-anemia therapy including recombinant human erythropoietin (rHuEPO) or roxadustat for more than 4 months were enrolled. RBC lifespan was measured by the RBC lifespan analyzer RBCS-01A depended on Levitt’s carbon monoxide (CO) breath test. Participants were primarily divided into low and high RBC lifespan groups by the average value.Result A total of 187 patients were included in this study. The average RBC lifespan was 65.2 ± 28.55 days. The logistic regression analysis indicated treating with roxadustat rather than rHuEPO [OR 2.94, 95% CI (1.46, 5.95), p < 0.01], male [OR 2.15, 95% CI (1.08, 4.29), p = 0.03], higher body mass index (BMI) [OR 1.17, 95% CI (1.07, 1.27), p < 0.01], and higher total iron-binding capacity (TIBC) [OR 1.04, 95% CI (1.01, 1.06), p = 0.01] were independent risk factors for the shorten of RBC lifespan. While higher adjusted calcium [OR 0.14, 95% CI (0.03, 0.70), p = 0.02] and older age [OR 0.96, 95% CI (0.94, 0.99), p = 0.01] were independent protective factors.Conclusion This study demonstrated that independent risk factors contributing to this reduction in RBC lifespan include male, elevated BMI, increased TIBC, and decreased adjusted calcium levels. Additionally, the type of anti-anemia therapy administered appears to have an impact on RBC lifespan.